Factors Affecting the Disclosure of Corporate Social Responsibility - Umi Kalsum (International Journal of Business Economics (IJBE), 2021)
This study aims to determine the factors that influence the extent of disclosure of social responsibility (Corporate Social Responsibility) by examining the influence of the board of commissioners, the board of directors, the audit committee, leverage, company size and profitability. The sample of this research is the LQ45 companies listed on the Indonesia Stock Exchange for the period 2018-2020. This study uses a quantitative approach with multiple linear regression analysis methods. The results of this study indicate that the board of commissioners' variables simultaneously, leverage, company size and profitability have the same significant effect on CSR disclosure. The results carried out partially show that the board of commissioners variables, company size and profitability have a significant and significant relationship to CSR disclosure, while leverage shows that it does not have a significant effect on CSR disclosure.